2012
DOI: 10.1177/0734016812467198
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Outlets, Social Disorganization, Land Use, and Violence in a Large College Town

Abstract: This study examined the direct and moderating effects of alcohol outlet density, social disorganization, and land use on violence in a large college town whose economy is driven by the presence of a flagship state university. Empirical literature points to a consistent association between alcohol outlet density and assault density, and recent research has found social disorganization and land use to moderate the association in urban areas. However, little research has been done to determine whether similar ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Between our off premises counts and on-premises patron capacity, we calculated an insignificant (p > 0.05), and low correlation (<0.30 correlation coefficient). These results show that congruent with other studies, our GLM model showed that bars and pubs have a greater factor increase on assault and disorder crime compared to off-premises licenses or other on-premises establishments [2,3,22,23,40,[42][43][44][45]. The locations of bars and pubs within DAs, and in neighboring DAs units (lag), had a significant association with (p < 0.05) assault and disorder crime counts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Between our off premises counts and on-premises patron capacity, we calculated an insignificant (p > 0.05), and low correlation (<0.30 correlation coefficient). These results show that congruent with other studies, our GLM model showed that bars and pubs have a greater factor increase on assault and disorder crime compared to off-premises licenses or other on-premises establishments [2,3,22,23,40,[42][43][44][45]. The locations of bars and pubs within DAs, and in neighboring DAs units (lag), had a significant association with (p < 0.05) assault and disorder crime counts.…”
Section: Discussionsupporting
confidence: 90%
“…These limitations make it hard to distinguish individual establishment effects [31][32][33][34][35][36][37][38][39]. Other studies separate establishment types (on verses off premises), but do not differentiate between establishment size [2,3,22,23,[40][41][42][43][44][45]. One study represents on-premises alcohol licenses by size (patron seats), but uses a hypothetical change in alcohol establishment locations to indicate rises in crime [46].…”
Section: Introductionmentioning
confidence: 99%
“…Given that a majority of the sample was not of legal age to purchase alcohol, an investigation of whether under-enforcement of existing policies is associated with polysubstance use is warranted. However, researchers often envision alcohol outlets as correlates of social disorganization (58), which provides an alternative explanation. Residence in an area of high drug crime density increases the probability of membership in the alcohol/marijuana class, relative to the marijuana-only class.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we were unable to control for other retail outlets that may contribute to the observed effects of alcohol outlets on non-violent crimes due to bringing potential offenders and victims together in retail areas. However, prior studies have shown that the effect of alcohol outlets on crime rates remains, even when controlling for land use and for the presence of other retail outlets Snowden and Pridemore 2013b). Lastly, our data do not allow us to examine the proximity of alcohol outlets to main streets, intersections, or bus stops, all of which could also contribute to neighborhood levels of thefts from vehicles and vandalism of property.…”
mentioning
confidence: 73%
“…We operationalized social disorganization as an index consisting of four traditional measures of social disorganization: poverty, residential instability, single-headed households, and ethnic heterogeneity. This approach follows those utilized by prior alcohol availability studies from criminology, sociology, epidemiology, and public health (e.g., Benson et al 2004;Emerick et al 2014;Nielsen, Martinez, and Lee 2005;Pridemore and Grubesic 2012;Roman et al 2008;Snowden and Pridemore 2013b). While there are many slight variations using measures from the U.S. Census, we used very frequently used measures that capture classical (Shaw and McKay 1942) Our measure of poverty -calculated based on the proportion of individuals in the block group with income below poverty level -was consistent with the measurement of poverty carried in our prior studies.…”
Section: Control Variablesmentioning
confidence: 99%